2020
DOI: 10.1016/j.clinimag.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) diagnostic technologies: A country-based retrospective analysis of screening and containment procedures during the first wave of the pandemic

Abstract: Since first report of a novel coronavirus in December of 2019, the Coronavirus Disease 2019 (COVID-19) pandemic has crippled healthcare systems around the world. While many initial screening protocols centered around laboratory detection of the virus, early testing assays were thought to be poorly sensitive in comparison to chest computed tomography, especially in asymptomatic disease. Coupled with shortages of reverse transcription polymerase chain reaction (RT-PCR) testing kits in many parts of the world, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 67 publications
1
42
1
5
Order By: Relevance
“…In fact, CT is a more sensitive means of evaluation of pulmonary parenchymal distortion. However, the choice of imaging modality depends on the clinical scenario and healthcare resources [27][28][29][30].…”
Section: Possibility Of Long-term Pulmonary Abnormalitiesmentioning
confidence: 99%
“…In fact, CT is a more sensitive means of evaluation of pulmonary parenchymal distortion. However, the choice of imaging modality depends on the clinical scenario and healthcare resources [27][28][29][30].…”
Section: Possibility Of Long-term Pulmonary Abnormalitiesmentioning
confidence: 99%
“…Chest CT with about 97% sensitivity has been extensively employed in the diagnosis and follow-up of patients with COVID-19, while RT-PCR with high specificity is the confirmative test for the diagnosis. Although some scientific advisors do not agree with the role of chest CT as a routine screening modality in this setting, it has been playing a key role in many healthcare settings due to the inadequacy of laboratory kits for diagnosis and more availability of CT [16][17][18][19]. More recently, with the wide availability of RT-PCR kits, CT is mainly used for the evaluation of COVID-19 complications and suspect alternative diagnoses [20].…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for this protective effect is that CT scans have led to earlier detection of the disease, as early reports describe characteristic imaging features that are helpful in aiding diagnosis [43]. This may have been particularly advantageous in developing countries, where the capacity to develop and mass-distribute testing was limited during the first months of the pandemic [43][44][45], as well as for frontline providers in any country irrespective of testing ability as a means of providing earlier diagnosis [46,47]. Countries with more radiologists and CT scanners per capita are also likely to have increased availability of other health resources, and thus the variables may serve as proxy for other factors that reflect the robustness of a nation's healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although our univariate analysis did not find a significant correlation between CFR and total radiologists or radiologists per one million, our data on radiologists per country was limited to one study from 2008 that included only 26 of the 39 countries analyzed [53]. More data is needed on this subject, as early reports on the global response to COVID-19 have shown that computerized tomography (CT) of the chest may serve an integral role in the timely diagnosis of the disease, as well as in severity staging and monitoring of clinical course [43,44,47,54,55]. Another limitation arises from utilizing data pertaining to entire countries for risk factors that may vary within each country on a geographically smaller scale-among cities, for example.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%